Phytoremediation: a sustainable environmental technology for heavy metals decontamination - Nedjimi, Bouzid (SN applied sciences, 2021)
Toxic metal contamination of soil is a major environmental hazard. Chemical methods for heavy metal's (HMs) decontamination such as heat treatment, electroremediation, soil replacement, precipitation and chemical leaching are generally very costly and not be applicable to agricultural lands. However, many strategies are being used to restore polluted environments. Among these, phytoremediation is a promising method based on the use of hyper-accumulator plant species that can tolerate high amounts of toxic HMs present in the environment/soil. Such a strategy uses green plants to remove, degrade, or detoxify toxic metals. Five types of phytoremediation technologies have often been employed for soil decontamination: phytostabilization, phytodegradation, rhizofiltration , phytoextraction and phytovolatilization . Traditional phytoremediation method presents some limitations regarding their applications at large scale, so the application of genetic engineering approaches such as transgenic transformation, nanoparticles addition and phytoremediation assisted with phytohormones, plant growth-promoting bacteria and AMF inoculation has been applied to ameliorate the efficacy of plants as candidates for HMs decontamination. In this review, aspects of HMs toxicity and their depollution procedures with focus on phytoremediation are discussed. Last, some recent innovative technologies for improving phytoremediation are highlighted.